Gothenburg Dialogue Corpus (GDC) - Språkbanken Text (University of Gothenburg, 2024)
Gothenburg Dialogue Corpus (GDC) is a collection of 360 individual dialogues
transcribed from recordings of about 25 different social activites. The
corpus was initiated in the late 1970's to meet a growing interest in
naturalistic spoken language data. The GDC data is very diverse considering
the different social activities with regard to punctuation, grammar,
vocabulary and the role of language and communication in human social life.
The corpus consist of both audio (50%) and audio/video (50%) recordings of
naturalistically occurring interactions.
For access please contact data@flov.gu.se.
Contains information about spoken language.

Gothenburg Dialogue Corpus (GDC) är en samling av 360 individuella dialoger
transkriberade från inspelningar av cirka 25 olika sociala aktiviteter.
Korpusen initierades i slutet av 1970-talet för att möta ett växande intresse
för naturalistiska talspråksdata. GDC-data är mycket varierande med tanke på
de olika sociala aktiviteterna med avseende på interpunktion, grammatik,
ordförråd och språkets och kommunikationens roll i mänskligt socialt liv.
Korpusen består av både ljud (50%) och ljud/video (50%) inspelningar av
naturligt förekommande interaktioner.
För åtkomst kontakta data@flov.gu.se.
Innehåller data om talspråk.
Gothenburg Dialogue Corpus (GDC)
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik